2002
DOI: 10.1021/nl0257418
|View full text |Cite
|
Sign up to set email alerts
|

Charge Generation Kinetics and Transport Mechanisms in Blended Polyfluorene Photovoltaic Devices

Abstract: We report a compositional analysis of blended hole-accepting and electron-accepting polyfluorene related materials, poly(9,9‘-dioctylfluorene-co-bis-N,N ‘-(4-butylphenyl)-bis-N,N ‘-phenyl-1,4-phenylene-diamine) [PFB] and poly(9,9‘-dioctylfluorene-co-benzo-thiadiazole) [F8BT], in films and in photovoltaic devices. We find that photoluminescence quenching is insensitive to blend composition but the photovoltaic quantum yield is strongly composition dependent. This indicates that charge transport, and not charge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
197
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(217 citation statements)
references
References 13 publications
17
197
0
1
Order By: Relevance
“…The elimination of the nanoscale defect structures from morphologies D to F causes an increase of about 1.23% in the PCE, 24% in the IQE, and 55% in the charge transport efficiency under real-circuit conditions. These observations are in agreement with the experimental findings of Snaith et al, 39 who found through composition analysis and photoluminescence emission spectroscopy experiments on PFB/F8BT-polymer blends that the process of charge transport and not the process of charge generation is the limiting factor of the device performance. We should also point out in this context that several recent experimental and theoretical studies 4,27,37,38,40,42 have demonstrated that structural characteristics can strongly affect the processes of charge generation and recombination as well as charge transport to the electrodes.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The elimination of the nanoscale defect structures from morphologies D to F causes an increase of about 1.23% in the PCE, 24% in the IQE, and 55% in the charge transport efficiency under real-circuit conditions. These observations are in agreement with the experimental findings of Snaith et al, 39 who found through composition analysis and photoluminescence emission spectroscopy experiments on PFB/F8BT-polymer blends that the process of charge transport and not the process of charge generation is the limiting factor of the device performance. We should also point out in this context that several recent experimental and theoretical studies 4,27,37,38,40,42 have demonstrated that structural characteristics can strongly affect the processes of charge generation and recombination as well as charge transport to the electrodes.…”
Section: Resultssupporting
confidence: 93%
“…Recent experiments indicate that such structural characteristics can strongly affect the complementary processes of charge generation and charge recombination as well as the process of charge transport to the electrodes. For example, Coffey and Ginger 37,38 observed very recently with time-resolved electrostatic force microscopy that, contrary to the common belief, 39 the domain centers of their DA-polyfluorene blends provide a much greater contribution to the photocurrent than the region in close proximity to the DA heterojunctions. They explained their observations by the mixing of the D-or A-rich phases with a minority fraction of the other component, which affects charge generation as well as charge transport.…”
Section: Introductionmentioning
confidence: 97%
“…Geminate recombination, bimolecular recombination, and space-charge effects can all play a role, 16 and the exact effect of morphology on each of these processes is still the subject of debate. 17 Further research is required to identify the exact physical origin of the full current-voltage curve, in particular the factors which determine the open-circuit voltage 18 and fill factor. 19 Computational modeling offers a way of investigating these issues and informing ongoing experimental work.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Next to PLEDs, F8BT is also used as active electron donating material in polymer/polymer solar cells, where it is blended with other fluorene based copolymers. [8][9][10][11][12] Furthermore, F8BT has a relatively high electron affinity ͑ϳ3.3 eV͒ and a large ionization potential of ϳ5.9 eV. As a result it can also be used as an electron-acceptor in allpolymer bulk heterojunctions.…”
mentioning
confidence: 99%